Preparation of copper nano lubricant for high end application - Muhammad Khairuddin, Pawiran (2012)
This paper presents a novel two step method for preparing of copper nano lubricants and aluminium nano lubircants by dispersing these two sample with refrigeration lubricant in ultrasonic vibrator. Different concentration of nanofluid were used in this experiment. Kinetic viscosity of nanoparticles inside the mixture was measured by viscometer and transmission electron microscope ( TEM ). As a result, the nanoparticles size must be in the spec which 1x10^(-9). This kind of particles can only be measured by TEM. By this way , we can see either these oil has the same viscosity or not. There was no considerable change in the kinematic viscosity of nano-oil at the various volume fractions of nanoparticles, indicating that the kinematic viscosity of nano-oils is a weak function of oil temperature considered. Effect of heating was considered as the temperature used in viscometer is in range 25 - 80°c.